Akuntabilitas Masjid Berdasarkan Isak 35 di Wilayah Kecamatan Kedungbanteng, Kabupaten Banyumas - Sully Kemala Octisari; Tjahjani Murdijaningsih; Haina Idam Suworo (Universitas Batanghari Jambi, 2021)
The purpose of this study was to determine the accountability and suitability of the financial reporting of mosques institutions in the Kedungbanteng sub-district with ISAK 35. This study used 14 samples of mosques in the Kedungbanteng sub-district. The method used in this research is descriptive qualitative method. The results of this study indicate that the Takmir (management) of the mosque in the Keungbanteng sub-district has managed the mosque’s finances accountably according to predermined criteria. Record keeping is done well even though it is still simple. Regarding the Interpretation of Financial Accounting Standards (ISAK) 35 mosque administrators have not kept records based on the standards issued by the Indonesian Institute of Accountants (IAI). The standard has not been applied because it is admittedly unheard of and introduced to mosque administrators.